2018
DOI: 10.2196/jmir.9110
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From a Living Lab on the Broad Adoption of eHealth in Primary Health Care

Abstract: BackgroundElectronic health (eHealth) solutions are considered to relieve current and future pressure on the sustainability of primary health care systems. However, evidence of the effectiveness of eHealth in daily practice is missing. Furthermore, eHealth solutions are often not implemented structurally after a pilot phase, even if successful during this phase. Although many studies on barriers and facilitators were published in recent years, eHealth implementation still progresses only slowly. To further unr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 30 publications
0
73
0
1
Order By: Relevance
“…The potential useful adoption of eHealth seems thus more facilitated in decentralized health systems, where local governance can allow integrated care initiatives which are more tailored on local/specific needs, with the help of new technologies. In particular, when patients, professionals, entrepreneurs, and government collaborate together, starting in local communities with few initial eHealth tools, the potential of eHealth can be "enforced" [100]. Furthermore, a greater adoption of eHealth seems to emerge where a NHS model are provided, that is with a tax-based financing system and with healthcare incentives which seem more favorable to eHealth implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential useful adoption of eHealth seems thus more facilitated in decentralized health systems, where local governance can allow integrated care initiatives which are more tailored on local/specific needs, with the help of new technologies. In particular, when patients, professionals, entrepreneurs, and government collaborate together, starting in local communities with few initial eHealth tools, the potential of eHealth can be "enforced" [100]. Furthermore, a greater adoption of eHealth seems to emerge where a NHS model are provided, that is with a tax-based financing system and with healthcare incentives which seem more favorable to eHealth implementation.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite, more general/national/international care programs, which are often related to temporary research projects and not based on local political/social policies, are more widespread in centralized countries and with weak PC, where the power for public health planning is not delegated to local/regional authorities but managed by the national/central government. Drawing on literature, we know that often adoption of eHealth applications ends when also related research projects are concluded, although successful [100], and that local health problems often require local solutions, with a crucial role of local research in providing adequate funds supporting local priorities [101]. In such a context, a strong PC represents the first…”
Section: Main General Aspects Of Programs Adopting Ehealthmentioning
confidence: 99%
“…Meanwhile, many new products are being introduced which do not clearly fit the current regulatory framework, so a dialogue with the right regulatory agencies can accelerate the time to market. Companies need to consider not only current regulations but also future regulations going to be initiated in the next 5 years or so [78]. Public-private partnerships are seen as growing driving forces in the quest for the development of innovative healthcare both in the USA and the EU.…”
Section: Certainty and Collaborative Frameworkmentioning
confidence: 99%
“…Despite its potential and a rapidly growing number of tools available, there continues to be barriers in the uptake and integration of e‐Health into practice (Moore et al, ; Swinkels et al, ). Even telehealth, which has enormous potential to bridge geographical access barriers, has been slow to achieve widespread adoption in some settings (Dorsey & Topol, ; Moore et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential and a rapidly growing number of tools available, there continues to be barriers in the uptake and integration of e-Health into practice (Moore et al, 2017;Swinkels et al, 2018).…”
mentioning
confidence: 99%